Selective and generic photocatalytic oxidation of alcohol with Pd-TiO2 thin films: butanols to butanal/butanone with different morphologies of Pd and 0.5 theta(Pt)-Pd counterparts - Salgaonkar, Kranti N.; Kale, Sandip R.; Nalajala, Naresh; Mansuri, Sayana; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2023)
The present study reports on the photocatalytic oxidation of butanols to butanal/butanone using thin film form of facet-dependent nano-Pd supported on commercial TiO2 under one-sun condition and demonstrates the generic nature. Pd-nanocube (Pd-NC(100)), Pd-truncated octahedron (Pd-TO (100) and (111)), polycrystalline (Pd-PC), and their counterparts with half-a-monolayer Pt-coated on Pd (0.5 theta(Pt)-Pd)) have been used as co-catalyst. A potentially scalable thin film form of Pd/TiO2 photocatalyst, prepared by drop-casting method, has been employed to study oxidation of n-butanol, 2-butanol, and iso-butanol to corresponding aldehyde/ketone. 100% selectivity is demonstrated to respective aldehyde/ketone with any catalyst used in the present study with varying degree of butanols conversion by NMR. 0.5 theta(Pt)-Pd-TO/TiO2 shows the highest conversion of 2-butanol to butanone (13.6% in 4 h). Continuous 10 h of reaction with the most active 0.5 theta(Pt)-Pd-TO/P25 catalyst demonstrates 31% conversion of 2-butanol to butanone, and catalyst recyclability has been demonstrated. The present protocol can be scalable to large scales to maximize the conversion in direct sunlight. Due to its generic nature, the current method can also be applied to many other alcohols and substrate molecules.
Keywords: energy conversion; Nanomaterials; Oxidation; Photocatalysis; Sustainability